The genus Grammothelopsis (Aphyllophorales, Basidiomycota) - Robledo, Gerardo Lucio (2007)
A synopsis of Grammothelopsis Jülich (Aphyllophorales, Basidiomycota) is provided and G. neotropica Robledo & Ryvarden is described as new.